Multi Criteria Decision Making Approach in Determining the Best Online Streaming Platform for Alpha Generation - Wahidin , Ahmad Jurnaidi; Prambodo, Yoga Listi; Asruddin, Asruddin (Yayasan Sraddha Panca Widya Nusantara, 2024)
This research aims to determine the best online streaming platform for Generation Alpha using a Multi-Criteria Decision Making (MCDM) approach that combines the Analytical Hierarchy Process (AHP) and Weighted Product (WP) methods. The criteria evaluated include free nature, flexibility, ease of use, content diversity, and privacy security. Through the AHP model, the weights of the criteria were determined and used in the WP method to rank the alternatives. The results show that YouTube is the best platform with the highest preference value, followed by Netflix and Disney+ Hotstar. The combination of AHP and WP methods allows for more objective and scalable decision-making, providing relevant recommendations for users and developers of streaming platforms. The model also has the potential to be applied in other multi-criteria evaluation contexts.